2021
DOI: 10.3390/ijerph18168781
|View full text |Cite
|
Sign up to set email alerts
|

Physical Functioning, Depressive Symptoms, and Suicidal Ideation among Older Korean Adults

Abstract: Previous studies have shown that the physical functioning of older adults directly affects their depressive symptoms, and suicide is also closely associated with depression. This study determined the effects of physical functioning on depressive symptoms and suicidal ideation among older Korean adults. This study used data from the 2017 National Survey of Older Persons. Among the 10,299 participants in the entire data set, 10,083 participants were analyzed, excluding 216 participants who did not respond to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
4
3
0
1
Order By: Relevance
“…Another finding of this study was that IADL was a variable influencing suicidal ideation. The result was similar to the results of previous studies that examined the association between suicidal ideation and IADL [ 36 , 37 ]. Sim et al, (2021) [ 38 ] determined the effects of physical functioning on depressive symptoms and suicidal ideation among older Korean adults, finding that limitations to instrumental activities of daily living (IADL) were significantly associated with increased suicidal ideation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Another finding of this study was that IADL was a variable influencing suicidal ideation. The result was similar to the results of previous studies that examined the association between suicidal ideation and IADL [ 36 , 37 ]. Sim et al, (2021) [ 38 ] determined the effects of physical functioning on depressive symptoms and suicidal ideation among older Korean adults, finding that limitations to instrumental activities of daily living (IADL) were significantly associated with increased suicidal ideation.…”
Section: Discussionsupporting
confidence: 90%
“…The result was similar to the results of previous studies that examined the association between suicidal ideation and IADL [36,37]. Sim et al, (2021) [38] determined the effects of physical functioning on depressive symptoms and suicidal ideation among older Korean adults, finding that limitations to instrumental activities of daily living (IADL) were significantly associated with increased suicidal ideation. Specifically, compared to those with non-limited IADL function, individuals with limitations were more likely to exhibit depressive symptoms and suicidal ideation, highlighting the critical role of physical functioning in older adults' mental health.…”
Section: Discussionsupporting
confidence: 87%
“…Depressive symptoms was found to be signi cantly correlated with self-neglect in disability elderly. Elderly with disabilities have a higher rate of depression than those without disabilities [23]. The results of the present study showed that the more depressive symptoms of disability elderly, the higher levels of self-neglect they have.…”
Section: Discussionsupporting
confidence: 47%
“…Many studies have been conducted in recent decades to explore the factors associated with suicidal ideation among different populations [ 15 , 16 , 17 , 18 ] as well as the effects of environmental factors on suicide, such as the community and family environment [ 19 , 20 , 21 , 22 , 23 ]. Regarding environmental factors, relatives are closely connected to people’s lives, and their behaviors, experiences, and emotions could affect individuals’ mental health, which had been confirmed in previous studies [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%